Marker assisted selection for developing superior breeding lines for white rust resistance in Indian mustard (Brassica juncea) using IP markers (Journal of Oilseed Brassica, 2026)
White rust caused by Albugo candida is one of the significant diseases for yield reduction in rapeseed-mustard. Molecular marker technology in combination with the traditional breeding method offers precise selection in crop improvement programme. RH0749 a commercial and susceptible variety of Indian mustard was crossed with resistant donors (Bio-YSR and BEC-144) for improving white rust resistance. BC1F1, BC2F1 populations were evaluated for various yield attributes and analysed at molecular level to undertake marker-assisted selection (MAS). Intron polymorphism and cleaved amplified polymorphic sequence markers were used for forward selection. Three IP markers in RH0749 × Bio-YSR cross and two IP markers in RH0749 × BEC-144 cross showed polymorphism. Three hundred and forty-eight SSRs were used for background selection and 72 SSR markers were found polymorphic in RH0749 × Bio-YSR cross while in RH0749 × BEC-144 cross, only 43 SSR markers were found polymorphic. The promising progenies (9 in BC2F1 for RH0749 × Bio- YSR and 8 in BC2F1 for RH0749 × BEC-144 cross) were selected based on molecular, morphological and disease data which can be further used in Indian mustard improvement programme for white rust resistance.